VISUAL DISABILITY IN INDIA: A LITERATURE REVIEW OF CHALLENGES, INTERVENTIONS, AND INCLUSIVE STRATEGIES (1990–2020) - Gill, Kawal (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Visual disability remains a significant public health and social concern in India, impacting millions of individuals across age groups, particularly in rural and underserved regions. This literature review critically examines the evolution of challenges and interventions related to visual impairment in India between 1990 and 2020. Drawing upon 39 data sources—including 29 peer-reviewed academic studies and 10 reports from government bodies and non-governmental organizations (NGOs)—the paper synthesizes key findings across five thematic domains: public health and prevalence, education and inclusion, assistive technology, community-based rehabilitation, and policy frameworks. Despite measurable progress in reducing preventable blindness through initiatives the National Programme for Control of Blindness and the implementation of the Rights of Persons with Disabilities Act (2016), significant barriers persist. These include lack of access to assistive technology, limited inclusive education, socio-economic stigma, and rural-urban disparities in service delivery. However, innovative interventions led by NGOs, emerging digital solutions, and participatory community models have shown promise in promoting inclusion. The review identifies persistent gaps in longitudinal data, regional research, and gender-disaggregated analysis. It concludes with actionable recommendations for policymakers, educators, technologists, and civil society stakeholders to foster an equitable and rights-based approach to visual disability in India.